O estresse ocupacional na disfunção temporomandibular e a resolutividade das teleconsultorias em dor orofacial no Brasil - Ricardo Luiz de Barreto Aranha (2022)
Temporomandibular dysfunctions (TMD) comprise a heterogeneous group of musculoskeletal conditions that reach the face in their masticatory structures, causing functional limitation or pain that makes up a category of orofacial pain. They have multifactorial etiology and are a public health problem. In turn, asynchronous teleconsulting in health aims to clarify health problems referred by health professionals to telehealth, including, among various aspects, the diagnostic and clinical procedures. With the advent of the COVID-19 pandemic, the service gained a new dimension, potentially remaining a relevant post-pandemic tool. The present work used two methodological approaches. The first aimed to develop a systematic review on the relationship between work stress – a stress category – and TMD. Searches were performed in Pubmed, Scopus, Web of Science, Lilacs, Embase, Google Scholar, and Opengrey databases. In addition, an analysis of the original articles' methodological quality and their association measures was carried out. By a cross-sectional study, the second evaluated the resolution of asynchronous national dental teleconsultations of the Telessaúde Brasil Redes Program. The secondary database of the Telehealth Results Monitoring and Evaluation System (SMART, in the Portuguese acronym) from 2019 to 2020 (before and after the COVID-19 pandemic) was used. The dichotomous variable “If referral to secondary care was avoided” was considered the outcome, compared with sex and professional covariates of the users, in addition to categories of the claims. A descriptive data analysis was developed using frequency data and a negative binomial regression model to estimate the unadjusted and adjusted prevalence ratios (PR) with the corresponding 95% confidence interval. As a result of the systematic review, 12 of 602 original articles were selected. Half found an association between work stress and TMD; ATM sounds (a DTM signal) and stress at work were associated only in a population of musicians. In addition, only three studies used validated tools for both stress and TMD. As for the cross-sectional study, a total of 2,629 teleconsultations were evaluated, of which 1,982 refer to 2019 (75.4%). In 2019, 1,522 (76.8%) avoided referral to secondary care, and in 2020, 373 (57.7%) did so. Dentists (33.1%) and physicians (55.1%) made up the majority of claimants, and dental doubts (39.6%) and “others” (58%) were the most frequent. In conclusion, given the limited number of articles and several methodological deficiencies, the systematic review showed minimal certainty of the evidence for the association between work stress and TMD. The cross-sectional study showed the effect of the Pandemic on the distribution of variables in the sample in 2020, as well as a higher resolution for women, dentists, and doubts associated with dentistry in the same period.